2010
DOI: 10.1007/s11259-010-9439-5
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of selected biochemical indicators of Equine Rhabdomyolysis in Arabian horses: pro-inflammatory cytokines and oxidative stress markers

Abstract: A total of 30 horses were divided into two groups, one served as a control whereas other was rhabdomyolysis diseased horses. After blood collection, the resulted sera were used for estimation of the activities of creatin kinase (CK), aspartate transaminase (AST), lactate dehydrogenase (LDH), lactic acid, triacylglycerol (TAG), glucose, total protein, albumin, globulin, urea, creatinine, Triiodothyronine (T(3)), calcium, sodium, potassium, phosphorus, chloride, vitamin E, interleukin-6 (IL-6) and tumor necrosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…This single result does not allow to hypothesize about the influence of breed or type of effort on the SAA level in horses with ER, nevertheless, it confirms the systemic effect of this muscle disorder. Another study by the same research team [ 22 ] indicated the significant increase in serum IL-6, TNF-α and PGF2-α in horses affected with ER. IL-6 is the main cytokine produced by the contracting skeletal muscle [ 23 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This single result does not allow to hypothesize about the influence of breed or type of effort on the SAA level in horses with ER, nevertheless, it confirms the systemic effect of this muscle disorder. Another study by the same research team [ 22 ] indicated the significant increase in serum IL-6, TNF-α and PGF2-α in horses affected with ER. IL-6 is the main cytokine produced by the contracting skeletal muscle [ 23 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown significant increase of IL-6 and other proinflammatory cytokines (IL-1β, TNF-α, interferon γ - INF-γ) in blood in human and horses after intensive or prolonged exercise [ 25 31 ]. Several authors proposed the stress-induced damage of muscle fibers as the main cause of blood cytokine increase after exercise, supported by the positive correlation between cytokines and muscle enzyme concentrations or the delayed onset muscle soreness (DOMS) [ 22 , 29 , 32 ]. Whereas direct link between exercise-related muscle damage and the induction of the APR still needs to be elucidated, the evidence of local cytokine production in muscle that leads to the systemic response may facilitate search for similar mechanism in other tissues of the musculoskeletal system.…”
Section: Discussionmentioning
confidence: 99%
“…Acute phase proteins (APP) are a positive (upregulated; Hp, Fb, SAA, ceruoloplasmin and α1-acid glycoprotein) or negative (downregulated; albumin, transferring and α-fetoproteins) response to stressful situations (LOUGHMILLER et al, 2007;GABAY and KUSHNER, 1999). Acute phase proteins (APP) and proinflammatory cytokines have been presented as prognostic and diagnostic biomarkers for many animal diseases by our team (EL-DEEB and EL-BAHR, 2010;EL-BAHR and EL-DEEB, 2013;EL-DEEB et al, 2014;EL-DEEB and EL-BAHR 2014a;EL-DEEB and EL-BAHR, 2014b). However, the investigation of these vital biomarkers in dairy cows in the peripaturient period has not been completely elucidated yet.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally certain serum cytokine concentrations (myokines) as well as c-reactive protein (CRP) are positively correlated with physiological muscle inflammation and damage during prolonged exercise in people; however they are less consistent in sled dogs ( 12 – 14 ). Horses with a history of ER show elevations of certain pro-inflammatory cytokines compared to a control group; however this has yet to be explored in dogs ( 15 ). Evidence of inflammation in dogs experiencing ER greater than an expected physiological response may reflect an underlying inflammatory disease or the beginnings of an acute phase response due to myonecrosis.…”
Section: Introductionmentioning
confidence: 99%